Protein–lipid co‐oxidation in emulsions stabilized by microwave‐treated and conventional thermal‐treated faba bean proteins. Issue 4 (16th April 2018) - Gürbüz, Göker; Liu, Chang; Jiang, Zhong‐qing; Pulkkinen, Marjo; Piironen, Vieno; Sontag‐Strohm, Tuula; Heinonen, Marina
Abstract: The course of protein–lipid co‐oxidation was investigated in oil‐in‐water emulsions stabilized with proteins extracted from microwave‐treated (MWT) and conventional thermal‐treated (CTT) faba beans stored at 37°C for 7 days. Emulsions prepared with proteins from untreated (UT) faba beans and soy protein isolate (SP) were monitored for comparison. Lipid oxidation was detected through formation of primary and secondary oxidation products while protein oxidation was examined via tryptophan fluorescence degradation in interface and aqueous phase. Oxidation of proteins was more emphasized in the interfacial layers of MWT, CTT, and SP emulsions than in UT emulsions due to the prominence of radical chain‐driven co‐oxidation mechanism while lipoxygenase (LOX) activity in UT and MWT emulsions resulted in high amounts of hydroperoxides and abundance in lipid oxidation volatiles. Conventional thermal treatment provided better oxidative stability than microwave treatment reflected in lower levels of hydroperoxides and relative lack of diversity in lipid volatiles. Among detected volatiles, formation of ketones was more distinguished in MWT, CTT, and SP emulsions while UT emulsions contained a more diverse range of alkenals and alkanals. Ketones are known to form mainly through radical recombination reactions which combined with the results of protein oxidation supports that radical transfer reactions between proteins and lipids were the driving force behind oxidation in MWT, CTT, and SP emulsions. Treatments of faba beans resulted in increased oxidative stability of emulsified lipids and lower degradation of aqueous phase proteins. Abstract : Proteins from faba beans undergone microwave and conventional thermal treatments were utilized in emulsion‐making. Co‐oxidation of protein and lipid constituents was monitored both in interfacial layer and continuous phase. Oxidation of interfacial proteins was more emphasized than those in continuous phase, while diversity of lipid oxidation volatiles was more prominent in emulsions prepared with proteins from untreated faba beans. Microwave‐treated samples provided better oxidative stability than conventional thermal‐treated ones.